An immunocytochemical study of malignant melanoma and its differential diagnosis from other malignant tumours. Issue 12 (December 1985) - Gatter, K C; Ralfkiaer, E; Skinner, J; Brown, D; Heryet, A; Pulford, K A; Hou-Jensen, K; Mason, D Y
Abstract : A series of 41 fresh and 36 routinely processed malignant melanomas were immunostained with a panel of 12 monoclonal antibodies reactive against a range of epithelial, lymphoid, and melanoma associated antigens. The aim of the study was to determine whether this panel of antibodies would be useful in diagnostically difficult cases for differentiating melanomas from other tumours, particularly carcinomas and lymphomas. The results confirmed that most unequivocal malignant melanomas can be identified by positivity for S100 protein and for the antigen recognised by antibody NK1/C3, and by negativity for epithelial and lymphoid antigens. The incidence of melanomas expressing cytokeratin antigens was higher, however, particularly in cryostat sections than has previously been reported. It is therefore suggested that a panel of antibodies with more than one marker in each category should be used for identifying melanomas in clinical practice.